2018
DOI: 10.1016/j.heliyon.2018.e00609
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of the beliefs of Japanese anti-influenza vaccination website authors

Abstract: BackgroundInfluenza vaccine coverage among the Japanese population is less than optimal. Anti-vaccination sentiment exists worldwide, and Japan is no exception. Anti-influenza vaccination activists argue on the internet that influenza vaccine has little or no efficacy and a high risk of side effects, and they warn that people should forgo vaccination. We conducted a qualitative analysis to explore beliefs underlying the messages of anti-influenza vaccination websites, by focusing on the perceived value these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
5
0
2
Order By: Relevance
“…Furthermore, the cumulative morbidity rate is relatively low, and behavioral restrictions are limited [ 21 ]. In the case of the influenza vaccine, a qualitative analysis of the beliefs of the authors of a Japanese anti-vaccine website revealed that they were not believers in conspiracy theories but that their anti-vaccine attitudes were motivated by two primary concerns: people’s “safety” and “self-esteem” [ 26 ]. This background peculiarity may be related to the low odds ratio for “Compliance”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the cumulative morbidity rate is relatively low, and behavioral restrictions are limited [ 21 ]. In the case of the influenza vaccine, a qualitative analysis of the beliefs of the authors of a Japanese anti-vaccine website revealed that they were not believers in conspiracy theories but that their anti-vaccine attitudes were motivated by two primary concerns: people’s “safety” and “self-esteem” [ 26 ]. This background peculiarity may be related to the low odds ratio for “Compliance”.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained approval from the Ethics Committee of Saga University (No: R2-24) to conduct this study. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), 40-49, 50-59, 60-69, 70-79 years), occupation, area of residence, marital status (married, unmarried), presence of children, annual household income category (below or above JPY 4 million), highest educational qualification (high school, vocational school, or university), height and weight, underlying diseases, and smoking status. Participants were also asked whether they or their close relatives had ever been infected with COVID-19, whether they had a history of close contact, and whether they had undergone polymerase chain reaction or antigen testing for detecting COVID-19.…”
Section: Survey Participants and Data Collectionmentioning
confidence: 99%
“…There were also concerns about pregnancy and the effects of vaccination on the future fetus, similar to influenza vaccination [26]. Okuhara et al showed that it was more effective to target vaccine-hesitant individuals rather than outright vaccine refusers because their attitudes toward vaccination are more amenable to change [27]. Before the first vaccination, the infection control team, which plays a major role in infection control in hospitals, such as the treatment of infectious diseases and countermeasures against resistant bacteria [28], was not able to provide adequate information on the COVID-19 vaccine to medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…According to many reports, inaccurate websites often appear among the top 10 results and provide erroneous information [ 21 , 22 ]. In the United Kingdom, Wikipedia sometimes appears more often in the search results than the National Health Service’s website [ 23 ].…”
Section: Discussionmentioning
confidence: 99%